2017
DOI: 10.1057/s41303-017-0066-x
|View full text |Cite
|
Sign up to set email alerts
|

Why security and privacy research lies at the centre of the information systems (IS) artefact: proposing a bold research agenda

Abstract: In this essay, we outline some important concerns in the hope of improving the effectiveness of security and privacy research. We discuss the need to reexamine our understanding of information technology (IT) and information system (IS) artefacts and to expand the range of the latter to include those artificial phenomena that are crucial to information security and privacy research. We then briefly discuss some prevalent limitations in theory, methodology, and contributions that generally weaken security/priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 157 publications
(49 reference statements)
4
120
1
1
Order By: Relevance
“…As mentioned by [61] in addition to the service offered by the technology itself, the interaction between provider and customer is necessary. Therefore, we address a substantial research investigation of privacy aspects in IoT, which is mentioned by [6] and [13] and whose relevance is particularly mentioned in the smart service context, e.g., by [61].…”
Section: Implications and Recommendations For Research And Practicementioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned by [61] in addition to the service offered by the technology itself, the interaction between provider and customer is necessary. Therefore, we address a substantial research investigation of privacy aspects in IoT, which is mentioned by [6] and [13] and whose relevance is particularly mentioned in the smart service context, e.g., by [61].…”
Section: Implications and Recommendations For Research And Practicementioning
confidence: 99%
“…Nevertheless, a major obstacle to adoption is the nature of the technology that gives rise to new concerns about information privacy [6]. An editorial in the Information Systems Journal stated that "recent technological changes are generating additional privacy challenges beyond the existing landscape" [7, p. 575].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found important cross-domain implications from ethical work climate to service outcome (Myer, Thoroughgood, & Mohammed, 2016), from climate regarding employee relations, organizational support, and leader-F I G U R E 1 An integrative model of information security policy (ISP) noncompliance member exchange to workplace safety (Hofmann & Morgeson, 1999;Wallace, Popp, & Mondore, 2006) and to customer service outcome (Schneider, White, & Paul, 1998). Researchers have also highlighted the relevance of ethics in the security, privacy, and IS domain (Lowry, Dinev, & Willison, 2017;Mingers & Walsham, 2010). Personal ethics and ethical work climate have both been found to directly or indirectly impact ISP (non)compliance (Hovav & D'Arcy, 2012;Li et al, 2014;Myyry et al, 2009;Yazdanmehr & Wang, 2016).…”
Section: Ethical Work Climatementioning
confidence: 99%
“…As a result of these events, ethical rules as they apply to academicians are being re-examined (Editorials Nature, 2018). Despite over a decade of research in privacy and security of information in IS (Acquisti & Gross, 2006;Lowry, Dinev, & Willison, 2017;Posey, Raja, Crossler, & Burns, 2017), we cannot assume that the problem is solved. A new approach to privacy and security may be necessary to overcome these challenges.…”
Section: Axiology: What Is Good and To Be Valued And What Should We mentioning
confidence: 99%